2000
DOI: 10.1080/027249800410463
|View full text |Cite
|
Sign up to set email alerts
|

Visual similarity effects in immediate verbal serial recall

Abstract: The role of visual working memory in temporary serial retention of verbal information was examined in four experiments on immediate serial recall of words that varied in visual similarity and letters that varied in the visual consistency between upper and lower case. Experiments 1 and 2 involved words that were either visually similar (e.g. fly, cry, dry; hew, new, few) or were visually distinct (e.g. guy, sigh, lie; who, blue, ewe). Experiments 3 and 4 involved serial recall of both letter and case from seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
63
3
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 0 publications
11
63
3
1
Order By: Relevance
“…The more confusable orthographic codes of the PsOs than of the PsOd characters, as evidenced by the objective index and subjective ratings of visual similarity, should still have resulted in worse memory performance in the former than in the latter condition. The findings of Experiment 2 ostensibly conflict with previous results that visually dissimilar words were remembered better than visually similar ones, especially when the pronunciations of these words were similar (e.g., Logie et al, 2000;Saito et al, 2008). The effect of shared phonetic radicals improving rather than hindering the WM of phonologically similar characters with a vertical structure might be due to the fact that the orthography of shared phonetic radicals facilitates character recognition in LTM but creates memory confusion in WM.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…The more confusable orthographic codes of the PsOs than of the PsOd characters, as evidenced by the objective index and subjective ratings of visual similarity, should still have resulted in worse memory performance in the former than in the latter condition. The findings of Experiment 2 ostensibly conflict with previous results that visually dissimilar words were remembered better than visually similar ones, especially when the pronunciations of these words were similar (e.g., Logie et al, 2000;Saito et al, 2008). The effect of shared phonetic radicals improving rather than hindering the WM of phonologically similar characters with a vertical structure might be due to the fact that the orthography of shared phonetic radicals facilitates character recognition in LTM but creates memory confusion in WM.…”
Section: Discussioncontrasting
confidence: 56%
“…Supporting the hypothesis of the WM model, Logie, Della Sala, Wynn, and Baddeley (2000) reported that immediate serial recall of words with different spellings (e.g., GUY, SIGH, and LIE) was better than that of words with similar spellings (e.g., CRY, DRY, and TRY). Similarly, immediate serial recall of both the identity and case of individual letters that were presented in either upper-or lowercase was better for letters whose upper-and lowercase variants were visually distinct (e.g., Hh, Rr, and Qq) than for letters whose upperand lowercase variants were visually identical except for size (e.g., Ww, Cc, and Kk).…”
supporting
confidence: 49%
See 2 more Smart Citations
“…Undoubtedly, more interference between sets at the time of memory maintenance would be obtained in studies with two stimulus sets of the same kind than with two different kinds (see for example Cowan and Morey, 2007; Oberauer, Lewandowsky, Farrell, Jarrold, & Greaves, 2012). It is of course also possible for visual stimuli to be encoded verbally (e.g., Conrad, 1964) or for verbal stimuli to be encoded visually (e.g., Logie, Della Sala, Wynn, & Baddeley, 2000), which would allow for more interference during maintenance, but any such recoding should be minimized by the presentation of verbal and visual stimuli on the same trial. Still, we used articulatory suppression to avoid verbal rehearsal of either stimulus set.…”
Section: A New Analytic Technique and Its Limitsmentioning
confidence: 99%